Ancient DNA shows high faunal diversity in the Lesser Caucasus during the Late Pleistocene. (1st September 2019) - Antonosyan, Mariya; Seersholm, Frederik V.; Grealy, Alicia C.; Barham, Milo; Werndly, Daniel; Margaryan, Ashot; Cieślik, Agata; Stafford, Thomas W.; Allentoft, Morten E.; Bunce, Michael; Yepiskoposyan, Levon
Abstract: In this study, we explore the Late Pleistocene (LP) vertebrate faunal diversity in south-eastern Lesser Caucasus based on morphological and genetic identification of fossil bones from Karin Tak cave. For the first time in this under-studied region, we used a bulk bone metabarcoding genetic approach to complement traditional morphology-based taxonomic identifications that are hampered by highly fragmented fossil bones. Excellent ancient DNA (aDNA) preservation allowed for a successful species identification of many bone remains and improved paleoenvironmental interpretations for the region. The aDNA identification of fossil bones revealed a high diversity of animal taxa inhabiting the region between ca. > 42, 000 and 25, 683–24, 803 calibrated years before present (cal. BP). Highlights: Insights into Late Pleistocene faunal diversity in the Lesser Caucasus. Assessment of prehistoric fauna of the region based on bulk bone metabarcoding. The MIS 3–MIS 2 transition did not cause a dramatic change in the faunal composition. Karin Tak provides possibility for molecular reconstruction of palaeoenvironment.